Tweaking palladium electronic structure to attain oxygen reduction activity superior to platinum/C - Sarma, Saurav Ch.; Kaja, Sai Manoj; Mishra, Vidyanshu; Vinod, Chathakudath Prabhakaran; Peter, Sebastian C. (ACS Applied Energy Materials, 2020)
Enhancing oxygen reduction (ORR) activity through alloying is crucial to improve the performance of a fuel-cell catalysts. In this work, we have studied the alloying effects of 4f rare-earth (RE) metals with palladium. The modified catalyst exhibits better activity (E-onset = 1 V and E-1/2 = 0.88 V) and higher selectivity toward H2O (similar to 97%) compared to the state-of-the-art catalysts due to complete dissociation of O-2. Hirshfeld charge analysis and 2D-electron localization function reveal improved adsorbate-adsorbent interaction on the catalyst surface. This work paves a strategy to design highly selective non-Pt-based catalysts for the ORR by controlling electronic structures and surface oxide formation.
Keywords: d-band center; DFT calculation; durability; EuPd; oxygen reduction reaction; YbPd

Metal deficiency tailored by the 18-electron rule stabilizes metal-based inorganic compounds - Singh, Ashutosh Kumar; Mumbaraddi, Dundappa; Mishra, Vidyanshu; Roy, Soumyabrata; Vinod, C. P.; Peter, Sebastian C. (Chemistry of Materials, 2023)
The 18-electron (18-e(-)) rule is typicallyrestrictedto predicting the stability of transition-metal-based complexes. Herein,we report the use of the 18-e(-) to predict the stabilityin a family of intermetallics MNiSn (M = V, Cr, Fe, and Co) crystallizingin the Co1.75Ge structure type. Site deficiencies at theM site obtained from single-crystal X-ray diffraction are understoodas attaining a stable noble gas electronic configuration. The densityfunctional theory -based structure calculation confirms that the deficientstructure is more stable than the ideal occupation available at thecrystal lattice. MnNiSn, which crystallizes in the half-Heusler crystalstructure, depicts the role of covalent radii of the constituent elementsin determining the crystal structure. Using X-ray absorption spectroscopyand X-ray photoelectron spectroscopy, the local structure of the above-mentionedcompounds was also elucidated, supporting the role of deficiency tunedvalence fluctuation to attain a 18-e(-) configurationthat eventually leads to the formation of stable compounds.